Prevalence, incidence, and factors associated with pre-stroke and post-stroke dementia: a systematic review and meta-analysis. - Pendlebury, S; Rothwell, P (2009)
BACKGROUND: Reliable data on the prevalence and predictors of post-stroke dementia are needed to inform patients and carers, plan services and clinical trials, ascertain the overall burden of stroke, and understand its causes. However, published data on the prevalence and risk factors for pre-stroke and post-stroke dementia are conflicting. We undertook this systematic review to assess the heterogeneity in the reported rates and to identify risk factors for pre-stroke and post-stroke dementia. METHODS: Studies published between 1950 and May 1, 2009, were identified from bibliographic databases, reference lists, and journal contents pages. Studies were included if they were on patients with symptomatic stroke, were published in English, reported on a series of consecutive eligible patients or volunteers in prospective cohort studies, included all stroke or all ischaemic stroke, measured dementia by standard criteria, and followed up patients for at least 3 months after stroke. Pooled rates of dementia were stratified by study setting, inclusion or exclusion of pre-stroke dementia, and by first, any, or recurrent stroke. Pooled odds ratios were calculated for factors associated with pre-stroke and post-stroke dementia. FINDINGS: We identified 22 hospital-based and eight population-based eligible cohorts (7511 patients) described in 73 papers. The pooled prevalence of pre-stroke dementia was higher (14.4%, 95% CI 12.0-16.8) in hospital-based studies than in population-based studies (9.1%, 6.9-11.3). Although post-stroke (